MENINGKATKAN MOTIVASI BELAJAR MELALUI MEDIA KONKRET DAN PEMBERIAN BINTANG PRESTASI - Sari, Putri; Andani, Putri; Pujianti, Pujianti; Fitri, Ramadini Eka; Hafizo, Rina; Rozana, Rozana; Camellia, Camellia; Juliana, Juliana (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2025)
Motivation to learn is needed in the learning process at school so that learning objectives can be achieved as expected. Learning motivation This research was conducted on the basis of findings of problems that arise in the school environment, especially in the education of elementary school children, namely related to students' learning motivation. This has been proven at school, where some children show a lack of enthusiasm and even do not want to participate in the learning process, for example children do not pay attention to the teacher's explanations and are busy telling stories with their friends. This problem demands the need for a learning media that provides Achievement Star rewards. The method used is a comparative descriptive method with a qualitative approach and a quantitative approach which aims to compare the motivation of students' learning levels without using achievement stars. This research involved 29 children. Data was collected through classroom observations during learning and documentation. Based on analysis of previous research data, it was found that before there was concrete media with awarding achievement stars, children were less enthusiastic about participating in learning activities. The research results show that using concrete media by giving Achievement Stars can motivate children's learning. For example, children are enthusiastic about learning, active when asking questions or asking questions during learning activities, carrying out assignments given by the teacher until they are finished. By giving this achievement star, educators are helped so that they can increase children's learning motivation. The research results showed that there was an increase from pre-cycle, to cycle 1, then cycles II, and III. It can be seen from the percentage of students' learning motivation in the pre-cycle, 28% was categorized as very poor, in cycle I it was 51.72% categorized as poor, in cycle II it reached 69%, it was categorized as sufficient and in cycle III it reached 93.10%, it was categorized as very good. Thus, it can be stated that the application of learning using concrete media and achievement stars can increase students' learning motivation in class II Elementary School Civics learning